Hierarchy of cities in Peru for regionalization purposes - Arana Velarde, Freddy (2021)
Objective. To classify hierarchically the cities of Peru according to their importance for the regionalization processes. Methods. The study had a quantitative approach, simple descriptive design; as a data collection instrument, a city hierarchy card was applied, which measured the dimensions of demographic size, economic size and urban relevance; A factor analysis was made of cities with more than 50 thousand inhabitants, taking as a sample 42 cities in Peru, excluding Metropolitan Lima. Results. It was found as cities of first hierarchy: Arequipa in the south of the country, Trujillo, Chiclayo and Piura in the north, Cuzco in the south east and Huancayo in the center; in second hierarchy: Tacna, Ica, Chimbote, Iquitos, Pucallpa; third hierarchy Ayacucho, Moquegua and Huánuco. Conclusions.The cities that most influence the regionalization processes at the macro-regional level are: in the north Trujillo, in the south Arequipa, in the center Huancayo, in the south-east Cusco of the first hierarchical rank and in the east Iquitos of the second rank.